Research and calculation of magnetic system of built-in axle-box generators of freight cars - O. A. Lysenko; L. D. Fedorova; S. G. Shantarenko (Омский научный вестник)
The article deals with the issues of providing communication, as well as diagnostics and telemetry of freight cars. The growth of rail traffic is currently placing increased demands on the levels of safety, automation and an increase in the average speed of freight trains. These requests can be solved through the introduction of modern GSM communication systems and geolocation. At the present time, a system for detecting the descent of a freight car has been developed and is being tested, which makes it possible to record the descent within a few seconds and transmit a signal to the train driver via a radio channel. The systems for monitoring the location of wagons and locomotives are no less important. However, one of the current problems is the lack of autonomous power supplies for communication and diagnostic systems. Since wired power systems have a number of disadvantages, the article discusses the creation of a power source based on an alternator with permanent magnets. This generator is driven by energy from a wheelset. The article presents the results of a numerical experiment on the magnetic system of axle-box generators using the ElCut software.